Development of antibacterial dual active food packaging based on super water absorbent and ethanol emitter: Pengembangan kemasan pangan aktif ganda antibakteri berbasis super water absorbent dan etanol emitter - Nilatany, Asti; Kusumaningrum, Harsi Dewantari; Suyatma, Nugraha Edhi; Mulyanto, Rizky Nuur Berlianni; Yunus, Ade Lestari; Pratama, Indra Mustika; Sasmita, Hadian Iman; Lukitowati, Fajar; Benita, Ashri Mukti; Syahputra, Akhmad Rasyid; Oktaviani, Oktaviani; Nuryanthi, Nunung (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2025)
One way to extend shelf life and maintain the quality of fresh chicken meat is to implement an active packaging system. This research aimed to develop active packaging in the form of pads used in chicken meat with dual functions: Super Water Absorbent (SWA) as an adsorbent system and Ethanol Emitter (EE) as an antibacterial release system. The packaging in this study was first carried out by making SWA/EE with a ratio of 0, 4, and 2 (b/v). Furthermore, SWA/EE granules were inserted into non-woven PP bags to form an adsorbent active packaging pad. The experimental design used was a Randomized Group Design (RGD) with 2 factors, namely SWA/EE pad ratio 0, 4, and 2 (b/v) with non-pad as control and storage time (0, 1, 3, 5, and 7 days). Each treatment was repeated 3 times. The results showed that the SWA/EE ratio 4 (w/v) had better ethanol release and water absorption rate compared to other treatments. SWA/EE treatment with SWA/EE ratio of 4 (b/v) showed a significant difference on the anti-bacterial activity of S. aureus (34.58 mm) and total bacterial growth on storage days 3, 5, and 7, with the lowest value on day 3 (1.52 log CFU/g). SWA/EE treatment did not significantly different on the antibacterial activity of E. coli and total bacterial growth at day 1 storage. Packaging with an SWA-EE ratio of 4 (w/v) has the potential to be a double active packaging that can be used on fresh chicken meat.